Cotranslational secretion of diphtheria toxin and alkaline phosphatase in vitro: involvement of membrane protein(s). - Smith, W P (1980)
Crude messenger ribonucleic acid fractions isolated from Corynebacterium diphtheriae and Escherichia coli were translated in an E. coli in vitro protein-synthesizing system and yielded precursors of the secreted proteins diphtheria toxin and alkaline phosphatase, respectively. Addition of inverted E. coli inner membrane vesicles to the system during the initial stages of translation resulted in the intravesicular segregation of mature diphtheria toxin and alkaline phosphatase. Outer membrane vesicles or inner membrane vesicles whose cytoplasmic surfaces had been treated with pronase could not mediate transmembrane transfer of diphtheria toxin or alkaline phosphatase. However, inner membrane vesicles isolated from E. coli spheroplasts which had been treated with pronase and inner membrane vesicles complexed with ribosomes during pronase treatment were functional in transmembrane transfer. At temperatures below the phase transition of E. coli membranes, no intravesicular segregation of alkaline phosphatase or diphtheria toxin was observed. The precursor forms of each protein accumulated free from the vesicles. These results suggest that an inner membrane protein, exposed on the cytoplasmic surface, plays an integral role in secretion.